KEBANGKITAN ISLAM MUHAMMAD AL-MUSTIRY: KRITIK ATAS TRADISI DAN MODERNITAS - Mukhlis, Febri Hijroh (IAIN Ponorogo, 2016)
Abstrct: Islam is influential religion in the world. In spite of, that condition does not in line with the highest productivity level in developing Islamic studies. Traditionally, there are several communities that highest imitation and unchangeable. Even in the modern era with various scientific developments, modern Muslims are even more gregarious and fanatical groups. Political identity became a new problem in Islamic modernity, the loss of productivity due to fall asleep with the spirit of the identity of interest to mutual recriminations completely wrong. Muhammad al-Mustiry criticized both (tradition and modernity) by offering the idea of the importance of reading tradition histories, prioritizing knowledge. And the main aim is Islam gives its contribution to civilization development. Keywords: Islam, awakening, tradition, modernity.